APLIKASI METODE DOUBLE EXPONENTIAL SMOOTHING HOLT DAN ARIMA UNTUK MERAMALKAN VOLUNTARY COUNSELING AND TESTING (VCT) ODHA DI PROVINSI JAWA TIMUR - Suci Retno Ningtiyas (Universitas Airlangga, 2018)
Forecasting can be used to view events or trends in future. Counseling in VCT is the counseling activities provide by psychological support, information and knowledge on HIV/AIDS, to prevent HIV transmission, promoting responsible behavior changes. This article purposed to knew number of VCT on people living with HIV in East Java province and predicted number people living with HIV which recorded via the VCT in 2018 used best method. The unit of analysis in this research was the number of people living with HIV in East Java, data processed using method of Holt Double Exponential Smoothing and ARIMA. The results of forecasting data logging by VCT in people with HIV used method Holt Double Exponential Smoothing which alpha=0.710 and gamma=0.039 i.e MAPE=26.06, MAD=24.75 and MSD=1999.59.The alpha parameter value (level) and gamma (trend)retrieved from the way try and error. Meanwhile, ARIMA models qualifies stationerity data, white noise and residual Kolmogorov Smirnov was ARIMA (2, 1, 1) with error MAPE=45.148, MAD=91.75 and MSD=437781.8. Based on the value of MAPE, MAD and MSD that forecasting VCT was suitable to used Double Exponential Smoothing Holt. Double Exponential Smoothing Holt with α (alpha)=0.710 and γ (gamma)=0.039can produce MAPE=26.06, MAD=24, 75 dan MSD=1999.59 produce forecasting for the year 2018, Ft + m = St + btm F57 value + 6 = S57 + b56, obtained results for the month of January of the year of 2018 244.769. The number of people living with HIV was recorded through VCT fluctuating but trends to rise over time. The value of forecasting has grown trend. For other researchers, because this research is univariate case, more comprehensive should added with other variables.